Angiogenesis inhibition on glioblastoma multiforme cell lines (U-87 MG and T98G) by AT-101 - Burcu Cakar; Ugur Muslu; Emir Bozkurt; Harika Atmaca; Burcak Karaca; Bulent Karabulut; Ruchan Uslu (Journal of Oncological Sciences, 2018)
Aim: Glioblastoma multiforme (GBM) is the most common glial tumor. Angiogenesis which provides nutrient and oxygen support to proliferating cells play an essential role in GBM development, proliferation and metastasis. The development of antiangiogenetic agents is a promising treatment issue as blood vessels are essential for the vitality of tumor cells. AT-101 is -(−) enantiomer of gossypol having anti-proliferative effects on different cancer cell lines. In this study, the cytotoxicity effect of AT-101 on GBM cell lines (U-87MG ve T98G) was confirmed and also the impact of this drug on VEGF synthesis on these cell lines were evaluated at transcriptional and protein levels. Materials and methods: U-87 MG and T98 cell lines were treated with increasing concentrations (1–50 μM) of AT-101 for 72 h. Cytotoxicity was determined by xCELLigence (Roche). Apoptosis was detected by using ELISA and confirmed by caspase assay. VEGF and other proangiogenic factors expression were evaluated by angiogenesis array. Results: The cell vitality was constantly followed up in the experiment. The cytotoxicity of AT-101 in both cell lines increased significantly at 24 h. The IC-50 values of U-87 MG and T98 were 2.4 and 2.7 μM respectively. The VEGF mRNA levels decreased by 2.7 fold in U-87MG and 3 fold in T98G by treating these cell lines with AT-101 IC50 dose for 24 h. Conclusions: This study showed that AT-101 suppress VEGF on protein levels at U-87 MG and T98G cell lines and showed AT-101 might be a promising targeted agent in GBM treatment. Keywords: Glioblastoma multiforme, AT-101, Angiogenesis, VEGF